Investigating the ICT usage on Transparency in the Governance Processes at the Local Level in Southwestern Nigeria - Olawoyin Kayode Wakili; Kazeem Oyedele Lamidi (Journal of Governance and Public Policy, 2019)
This article discusses the nexus between ICT and transparency in local governance in Southwestern Nigeria. There appears to be little or no attempt at investigating the role of ICT usage in transparency in local governance in Southwestern Nigeria. This article takes this as a point of departure. The article relies on primary data sourced through mixed approach method of administering of questionnaire on local council ICT officers, registered voters, local community and youth leaders and key informant interview of officers of ICT non-governmental organisations. For the Quantitative design, 418 respondents were administered with questionnaire while 18 key informants were purposively interviewed. Data were analysed using SPSS; correlation co-efficient analysis using tables, while the interview responses were presented using content analysis. Results showed a positive correlation of +0.421 between ICT and transparency in local governance. The study concludes that local governance will better be enhanced through relevant ICT tools in rural communities.This article discusses the nexus between ICT and transparency in local governance in Southwestern Nigeria. There appears to be little or no attempt at investigating the role of ICT usage in transparency in local governance in Southwestern Nigeria. This article takes this as a point of departure. The article relies on primary data sourced through mixed approach method of administering of questionnaire on local council ICT officers, registered voters, local community and youth leaders and key informant interview of officers of ICT non-governmental organisations. For the Quantitative design, 418 respondents were administered with questionnaire while 18 key informants were purposively interviewed. Data were analysed using SPSS; correlation co-efficient analysis using tables, while the interview responses were presented using content analysis. Results showed a positive correlation of +0.421 between ICT and transparency in local governance. The study concludes that local governance will better be enhanced through relevant ICT tools in rural communities.